Glass yarn, glass cloth manufacturing method and glass cloth
By using glass yarns with specific parameters, including TEX, fracture strength and slip-off filaments, the problem of low dielectric glass cloth fluff quality deviation is solved, and high-quality and uniform glass cloth production is achieved.
Patent Information
- Application Number
- CN202210589113.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-27
- Filing Date
- 2022-05-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-05-26
AI Technical Summary
It is difficult to stably obtain high-quality low-dielectric glass cloth in the prior art, especially in the range of thicknesses of 10 to 50 μm, and the fluff quality is prone to large deviations.
The glass cloth is produced by using glass yarns within a specific range, specifically, the TEX of the glass yarn is 1 to 13, the breaking strength is 0.50 to 0.80 N/tex, and the number of filaments that slip to more than twice the average yarn width value at 180 m is measured to be 3 or less.
The production of glass cloth with high uniformity and good quality is achieved, reducing the generation of fluff in the weaving process and fiber opening process, and improving the in-plane uniformity of glass cloth and the uniformity between batches.
Smart Images

Figure BDA0003664349910000251 
Figure BDA0003664349910000261 
Figure BDA0003664349910000351
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing glass yarn and glass cloth and the glass cloth. Background Art
[0002] With the development of information communication society in recent years, data communication and / or signal processing are gradually being carried out with large capacity and high speed. As a result of using printed circuit boards in high-end servers, high-end routers / switches, supercomputers, communication equipment of base stations, measuring instruments, etc., the dielectric constant of printed circuit boards is being reduced. Therefore, regarding the glass cloth constituting the printed circuit board, a low dielectric glass cloth has been proposed. For example, Patent Document 1 discloses: For the E glass cloth that has been used so far, a large amount of boron trioxide (B 2 O 3 ), and adjust the silicon dioxide (SiO 2 ) and other ingredients, thereby achieving low dielectric constant of glass cloth.
[0003] As for terminal electronic devices such as smartphones, they are also required to cope with large-capacity and high-speed communications, and therefore, in recent years, it is expected that the dielectric constant of printed circuit boards used in smartphones will be further reduced. Therefore, there is a strong demand for thin (for example, 10 to 50 μm thick) low-dielectric glass cloth.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 11-292567
[0007] Patent Document 2: Japanese Patent Application Publication No. 2013-112917
[0008] Patent Document 3: Japanese Patent Application Publication No. 2004-115351
[0009] Patent Document 4: Japanese Patent Application Publication No. 2011-140721
[0010] Patent Document 5: International Publication No. 2018 / 216637 Summary of the invention
[0011] Problem that the invention aims to solve
[0012] As a result of research conducted by the present inventors, it was found that the low dielectric glass cloth described in Patent Document 1 has performance or quality variations compared to conventionally known E glass cloth. In particular, in low dielectric glass cloth having a thickness of 10 to 50 μm, the quality of the fuzz easily varies greatly, and therefore, it is difficult to stably obtain glass cloth having excellent fuzz quality.
[0013] As methods for improving the fluff quality of glass cloth, Patent Documents 2 and 3 disclose methods of using specific starch as a sizing agent for glass yarn, Patent Document 4 discloses a method of alleviating the bending of yarn in a wire ring during the manufacture of glass yarn, and Patent Document 5 discloses a method of using a low dielectric glass of a specific composition.
[0014] Patent Document 2 discloses that fuzzing of the cloth can be suppressed by producing glass cloth using glass yarn produced using a sizing agent containing 25 to 100% by mass of starch composed of amylose and having an average particle size of 12 μm or less.
[0015] Patent Document 3 discloses that the bundling property of the glass yarn can be improved by preparing a glass yarn to which 1.5 to 3.0 mass % of a sizing agent containing etherified high-amylose starch having an amylose content of 50% or more is attached, thereby effectively preventing the generation of fuzz.
[0016] Patent Document 4 discloses that in the twisting process of manufacturing glass yarn, the yarn passing portion of the bead ring is thickened to ease the bending of the yarn when passing through the bead ring, thereby making it difficult for quality defects such as fuzz, yarn breakage, and tangling to occur.
[0017] Patent Document 5 discloses that: by forming a glass composition expressed in weight % containing 50≤SiO 2 ≤56, 20≤B 2 O 3 ≤30、10≤Al 2 O 3 ≤20, 3.5≤MgO+CaO≤10 and 0≤R 2 O≤1.0 (wherein R is at least one element selected from Li, Na, and K), and further contains Fe 2 O 3 The low dielectric glass can suppress yarn breakage and fuzzing during glass yarn processing.
[0018] It is speculated that this is because low-dielectric glass yarn is weaker in strength than the E-glass glass yarn used in the past, and there is a large deviation in the quality of the fluff of glass cloth made using low-dielectric glass yarn available on the market. Therefore, the current situation is that low-dielectric glass yarn that can be used to stably obtain high-quality glass cloth has not yet been obtained.
[0019] For example, by using glass yarn with few defects, it is easy to improve the quality of glass cloth. In recent years, against the background of the improvement in the quality required for glass cloth, it is desired to provide glass cloth that can meet the expectation for such quality improvement. For example, low dielectric resins tend to have a higher molecular weight or a larger functional group, and sometimes have poorer impregnation of varnish than conventional resins. Therefore, there is a background of requiring high impregnation on the glass cloth side.
[0020] The present invention has been made in view of the above-mentioned problems, and its object is to provide a glass yarn with few defects, to provide a glass cloth with high uniformity and good quality using the glass yarn, and to provide a method for producing the same.
[0021] Solutions for solving problems
[0022] The present inventors have conducted intensive studies to solve the above-mentioned problems, and as a result, they have focused on the fact that microscopic hairs and the like can be detected first by predetermined visual observation, and have completed the present invention. One embodiment of the present invention is listed below.
[0023] [1] A glass cloth obtained by weaving glass yarns containing a plurality of glass filaments as warp yarns and weft yarns,
[0024] Taking 500 m in the length direction of the glass cloth as the object, white LED light is irradiated along its surface, and every 1 m in the length direction is observed. When there is fluff on the entire surface of the cloth, when the number of defects is counted as 1, the deduction rate expressed by the following formula is 0 to 3.5%.
[0025] Deduction rate (%) = (total number of defects / 500) × 100
[0026] [2] The glass cloth according to item 1, wherein the entire surface of the nap includes raised naps of 200 to 1000 μm caused by the breakage of the filaments observed on the cloth surface using an optical microscope.
[0027] [3] The glass cloth according to item 1 or 2, wherein the glass cloth has a thickness of 10 to 50 μm.
[0028] [4] The glass cloth according to any one of items 1 to 3, comprising the glass yarn satisfying the following conditions:
[0029] (i) TEX is 1 to 13;
[0030] (ii) a breaking strength of 0.50 to 0.80 N / tex; and
[0031] (iii) The number of filaments which slipped to twice or more of the average yarn width when measuring 180 m is 3 or less.
[0032] [5] The glass cloth according to any one of items 1 to 4, comprising the glass yarn having a twist interval length of 1.8 to 10.0 cm.
[0033] [6] The glass cloth according to any one of items 1 to 5, comprising the glass yarn having a value (twist interval length difference index) of 0.7 or less, the value obtained by dividing the difference between the maximum twist interval length and the minimum twist interval length of the glass yarn by the average twist interval length.
[0034] [7] The glass cloth according to any one of items 1 to 6, wherein
[0035] Taking the glass yarn having a length of 10,000 m or more as an object,
[0036] When a measurement range of 180 m in the longitudinal direction is selected at five different locations, the number of filaments that slipped to twice or more of the average yarn width is 3 or less in each of the five measurement ranges.
[0037] [8] The glass cloth according to any one of items 1 to 6, wherein
[0038] Taking the glass yarn having a length of 50,000 m or more as an object,
[0039] When a measurement range of 180 m in the longitudinal direction is selected at seven different locations, the number of filaments that slipped to twice or more of the average yarn width is three or less in each of the seven measurement ranges.
[0040] [9] The glass cloth according to any one of items 1 to 6, wherein
[0041] Taking the glass yarn having a length of 100,000 m or more as an object,
[0042] When a measurement range of 180 m in the longitudinal direction is selected at 10 different locations, the number of filaments that slipped to more than twice the average yarn width is 3 or less in each of the 10 measurement ranges.
[0043]
[10] A method for producing glass cloth, comprising the steps of using glass yarns containing a plurality of glass filaments as warp yarns and weft yarns and weaving the warp yarns.
[0044] (i) the TEX of the glass yarn is 1 to 13;
[0045] (ii) the breaking strength of the glass yarn is 0.50 to 0.80 N / tex; and
[0046] (iii) The number of filaments which slipped to twice or more of the average yarn width when measuring 180 m is 3 or less.
[0047]
[11] The method for producing glass cloth according to item 10, wherein the glass yarn has a TEX of 1 to 7.
[0048]
[12] The method for producing glass cloth according to item 10 or 11, wherein the number of glass filaments constituting the glass yarn is 30 to 120.
[0049]
[13] The method for producing glass cloth according to any one of items 10 to 12, wherein the twist interval length of the glass yarn is 1.8 to 10.0 cm.
[0050]
[14] A method for producing glass cloth according to any one of items 10 to 13, wherein the value obtained by dividing the difference between the maximum twist interval length and the minimum twist interval length of the glass yarn by the average twist interval length (twist interval length difference index) is less than 0.7.
[0051]
[15] The method for producing a glass cloth according to any one of items 10 to 14, wherein the density of the glass yarn is 2.2 g / cm 3 Above and less than 2.5g / cm 3 .
[0052]
[16] The method for producing glass cloth according to any one of items 10 to 15, wherein the elastic modulus of the glass yarn is 50 to 70 GPa.
[0053]
[17] The method for producing glass cloth according to any one of items 10 to 16, wherein the elastic modulus of the glass yarn is 50 to 63 GPa.
[0054]
[18] The method for producing a glass cloth according to any one of items 10 to 17, wherein
[0055] Taking the glass yarn having a length of 10,000 m or more as an object,
[0056] When a measurement range of 180 m in the longitudinal direction is selected at five different locations, the number of filaments that slipped to twice or more of the average yarn width is 3 or less in each of the five measurement ranges.
[0057]
[19] The method for producing a glass cloth according to any one of items 10 to 17, wherein
[0058] Taking the glass yarn having a length of 50,000 m or more as an object,
[0059] When a measurement range of 180 m in the longitudinal direction is selected at seven different locations, the number of filaments that slipped to twice or more of the average yarn width is three or less in each of the seven measurement ranges.
[0060]
[20] The method for producing a glass cloth according to any one of items 10 to 17, wherein
[0061] Taking the glass yarn having a length of 100,000 m or more as an object,
[0062] When a measurement range of 180 m in the longitudinal direction is selected at 10 different locations, the number of filaments that slipped to more than twice the average yarn width is 3 or less in each of the 10 measurement ranges.
[0063]
[21] A glass yarn, wherein:
[0064] (i) TEX is 1 to 13;
[0065] (ii) a breaking strength of 0.50 to 0.80 N / tex; and
[0066] (iii) The number of filaments which slipped to twice or more of the average yarn width when measuring 180 m is 3 or less.
[0067]
[22] The glass yarn according to Item 21, wherein the TEX is 1 to 7.
[0068]
[23] The glass yarn according to item 21 or 22, wherein the number of glass filaments constituting the glass yarn is 30 to 120.
[0069]
[24] The glass yarn according to any one of items 21 to 23, wherein the twist interval length is 1.8 to 10.0 cm.
[0070]
[25] The glass yarn according to any one of items 21 to 24, wherein the value obtained by dividing the difference between the maximum twist interval length and the minimum twist interval length by the average twist interval length (twist interval length difference index) is less than 0.7.
[0071]
[26] The glass yarn according to any one of items 21 to 25, wherein the density is 2.2 g / cm 3 Above and less than 2.5g / cm 3 .
[0072]
[27] The glass yarn according to any one of items 21 to 26, wherein the elastic modulus is 50 to 70 GPa.
[0073]
[28] The glass yarn according to any one of items 21 to 27, wherein the elastic modulus is 50 to 63 GPa.
[0074]
[29] The glass yarn according to any one of items 21 to 28, wherein
[0075] Taking the glass yarn having a length of 10,000 m or more as an object,
[0076] When a measurement range of 180 m in the longitudinal direction is selected at five different locations, the number of filaments that slipped to twice or more of the average yarn width is 3 or less in each of the five measurement ranges.
[0077]
[30] The glass yarn according to any one of items 21 to 28, wherein
[0078] Taking the glass yarn having a length of 50,000 m or more as an object,
[0079] When a measurement range of 180 m in the longitudinal direction is selected at seven different locations, the number of filaments that slipped to twice or more of the average yarn width is three or less in each of the seven measurement ranges.
[0080]
[31] The glass yarn according to any one of items 21 to 28, wherein
[0081] Taking the glass yarn having a length of 100,000 m or more as an object,
[0082] When a measurement range of 180 m in the longitudinal direction is selected at 10 different locations, the number of filaments that slipped to more than twice the average yarn width is 3 or less in each of the 10 measurement ranges.
[0083] Effects of the Invention
[0084] According to the present invention, a glass yarn having few defects can be provided, and a glass cloth having high uniformity and good quality can be provided by using the glass yarn, and a method for producing the glass cloth can also be provided. DETAILED DESCRIPTION
[0085] Hereinafter, an embodiment of the present invention (hereinafter referred to as “embodiment”) will be described in detail, but the present invention is not limited thereto and various modifications can be made without departing from the gist of the present invention.
[0086] 〔Glass cloth〕
[0087] The first embodiment of the present invention is a glass cloth.
[0088] The glass cloth of this embodiment is:
[0089] The glass cloth is obtained by weaving glass yarn containing multiple glass filaments (hereinafter also referred to as "filaments") as warp yarns and weft yarns. A specified measuring length of 500 (m) in the total length in the longitudinal direction of the glass cloth is taken as the object, and white LED light is irradiated along the cloth surface for every 1m in the longitudinal direction and observed. When the cloth surface has fuzz all over, when the number of defects is counted as 1, the deduction rate expressed by the following formula is 0 to 3.5%.
[0090] Deduction rate (%) = total number of piles on the whole surface / 500 (m) × 100
[0091] In this embodiment, by irradiating white LED light along the cloth surface and observing the cloth surface, it is possible to detect filament breaks (hereinafter also referred to as "micro-fluff") with a better sensitivity than the conventional observation by irradiating light in a perpendicular direction to the cloth surface. In addition, since the deduction rate derived from this detection method is 0 to 3.5%, the glass cloth has few disadvantages and, furthermore, has excellent various properties. From the same viewpoint, the deduction rate is preferably 3.0% or less, and more preferably 2.9% or less.
[0092] It should be noted that the previous observation (the previous observation achieved by irradiating the fabric surface with light in a vertical direction) did not envision the observation of fine hairs. Therefore, based on the previous observation method, it is impossible to detect the fine hairs envisioned in the present embodiment with good sensitivity, and further, it is not easy to control the deduction rate to the numerical range envisioned in the present embodiment.
[0093] The calculation method of "deduction rate (%)" is described in detail in the examples.
[0094] The full-surface fluff includes 200 to 1000 μm fluff caused by filament breakage observed on the fabric surface using an optical microscope. As shown in this embodiment, the full-surface fluff is easily observed by irradiating the fabric surface with white LED light and observing the fabric surface.
[0095] The glass cloth of the present embodiment preferably has a thickness described below. In addition, the glass yarn for obtaining the glass cloth of the present embodiment preferably has a structure described below.
[0096] (Dielectric constant of glass cloth)
[0097] The dielectric constant of the glass cloth is preferably 5.0 or less, more preferably 4.9 or less, further preferably 4.8 or less, and particularly preferably 4.6 or less at a frequency of 10 GHz. The dielectric constant of the glass cloth can be measured by a cavity resonance method. In this specification, the dielectric constant of the glass cloth refers to the dielectric constant at a frequency of 10 GHz unless otherwise specified.
[0098] 〔Glass yarn〕
[0099] The second embodiment of the present invention is glass yarn.
[0100] Regarding the glass yarn of the second embodiment,
[0101] (i) TEX is 1 to 13;
[0102] (ii) a breaking strength of 0.50 to 0.80 N / tex; and
[0103] (iii) The number of filaments that slipped to twice or more the average yarn width when measuring 180 m (hereinafter, "the number of filaments that slipped to twice or more the average yarn width when measuring 180 m" is simply referred to as "the number of slipped filaments") is 3 or less.
[0104] The quality of glass cloth made by using low dielectric glass yarn is different from that of conventional E glass cloth. Therefore, it is known that it is difficult to stably obtain high-quality low dielectric glass cloth. Among them, when the glass cloth with poor quality is studied in detail, a large number of "band-shaped fluff defects" in which the fluff is densely present in the length direction in the low dielectric glass yarn made by the low dielectric glass yarn whose number of slipped filaments deviates from a specific range are confirmed. In contrast, the present embodiment is based on the following insights: by using low dielectric glass yarn whose filaments fall off within a specific range, the disadvantage of low dielectric glass cloth can be reduced. This reason is not bound by theory, and it can be considered that: when the glass yarn whose filaments fall off is greater than a specific value (for example, the number of slipped filaments is greater than 3) is pulled out from the bobbin in the weaving process and passes through the weaving machine components such as the loop guide, it is easy to cause the filaments to fall off or break.
[0105] In particular, the weft yarn is transported with ballooning motion in the yarn path from being pulled out from the bobbin to being ejected. Therefore, it is believed that the filament slipping portion is easily subjected to shear stress and breaks, and the broken filament pieces are easily entangled due to the rotational motion and grow into coarse fluff. In order to improve productivity, the weft yarn insertion speed is preferably faster, but it is believed that the faster the weft yarn is transported, the more severe the filament shedding or the more likely the filament breakage will be.
[0106] The E-glass glass yarn used so far has a higher density and strength than the low-dielectric glass yarn. Therefore, the transportation of the glass yarn is stable, and the degree of interference with the weaving components is small, so the damage in the event of interference is limited. On the other hand, in the low-dielectric glass yarn that is lighter and has lower strength, there is a tendency for the deviation to become larger due to tension changes when the glass yarn is transported. Therefore, it is easy to interfere with the weaving components, and when it interferes with the weaving components, it is also easy to suffer greater damage. Therefore, it can be considered that it is easy to contribute to the aggravation of filament shedding or filament breakage.
[0107] In addition, when the glass yarn with filament shedding greater than a specific range is subjected to physical loads such as high-pressure spray water during the fiber-opening process, the shedding part is easy to move. Therefore, it can be considered that the shedding part is easy to bear loads such as interference with the conveying components of the glass cloth, and it is easy to generate fluff caused by filament breakage or fluff at the broken part with the shedding part as the starting point. In order to improve the in-plane uniformity of the glass cloth and improve the impregnation, it is preferred that the fiber-opening processing force is stronger, but it can be considered that the stronger the fiber-opening processing force, the more likely it is to generate more fluff defects caused by filament breakage or coarse fluff defects caused by filament entanglement.
[0108] Furthermore, the glass strength of low-dielectric glass yarn, which has a lower density and strength than E glass, decreases significantly in the heat cleaning process. Therefore, it is believed that when the fiber opening process is performed after the heat cleaning process, it is strongly damaged by physical loads such as high-pressure water spray, and it is more likely to cause fuzz caused by filament breakage or fuzzing of broken filaments. It is believed that these effects are manifested in the form of glass cloth quality.
[0109] On the other hand, by using the glass yarn of the present embodiment, even when using a glass yarn that is lighter and has lower strength after being low-dielectricized, it is possible to reduce the damage incurred when the glass yarn is pulled out and passed through a weaving machine component such as a ring guide during the weaving process and interferes with the weaving machine component. In addition, when using the glass yarn of the present embodiment, it is also possible to reduce the degree of interference between the falling part and the conveying component or the damage incurred during the interference during the fiber opening process. Therefore, by using the glass yarn of the present embodiment, it is possible to suppress the generation of fluff caused by filament breakage in the weaving process and the fiber opening process, and obtain a good quality and uniform glass cloth. In addition, by using the above-mentioned glass yarn, there is a tendency to increase the weaving speed (glass yarn weaving speed) and / or the fiber opening processing force in the fiber opening process, so it is preferred.
[0110] When the glass yarn of this embodiment is used, in the process of pulling out the glass yarn (e.g., warp yarn) from the bobbin raw yarn using a creel and straightening it, it is possible to prevent the generation of defects such as fluff when being rubbed by a yarn path guide, etc., so there is a tendency that the quality is good and stable production can be achieved, so it is preferred. In addition, by using the above-mentioned glass yarn, there is a tendency that the warping speed can be increased, so it is preferred.
[0111] (Glass yarn TEX)
[0112] The TEX of the glass yarn is 1 to 13, preferably 1.5 to 12, more preferably 2.0 to 11, and further preferably 2.5 to 10 or 1 to 7. If the TEX of the glass yarn is 13 or less, the strength of the glass yarn is low, and therefore, there is a tendency that the glass yarn interferes with the weaving machine components when passing through the ring guide and other weaving machine components in the fiber opening process, and interferes with the conveying components of the glass cloth in the fiber opening process, thereby easily causing fluff defects. On the other hand, by adjusting the degree of filament shedding within the specific range of the present embodiment, the above-mentioned degree of interference or damage sustained during interference can be reduced, and as a result, high-quality glass cloth can be obtained stably. By making the TEX of the glass yarn greater than 1, when the degree of filament shedding is within the specific range of the present embodiment, it is possible to suppress the breakage of the filaments when the glass yarn interferes with the weaving machine components when passing through the ring guide and other weaving machine components in the fiber opening process, and when the filaments interfere with the conveying components of the glass cloth in the fiber opening process.
[0113] (Breaking strength of glass yarn)
[0114] The breaking strength of the glass yarn is 0.50 to 0.80 N / tex. The preferred range of the breaking strength is 0.53 to 0.79 N / tex, the more preferred range is 0.57 to 0.78 N / tex, and the further preferred range is 0.60 to 0.77 N / tex. If the breaking strength of the glass yarn is above the above lower limit, the filaments are not easy to break and fuzz is not easy to generate when the glass yarn is pulled out and passed through the weaving machine components such as the ring guide in the weaving process and interferes with the conveying components of the glass cloth in the fiber opening process and is subjected to shear stress. On the other hand, if the breaking strength of the glass yarn is below the above upper limit, there is a tendency that the deviation of the yarn or the balloon movement in the yarn conveying process until the glass yarn is pulled out from the bobbin and ejected is suppressed to a smaller extent, and as a result, it is not easy to cause the filament to fall off or the fuzz defect caused by the filament breakage. It is speculated that this is based on the effect of the ductility of the glass yarn.
[0115] (Number of slipped filaments of glass yarn)
[0116] The number of slipped filaments of the glass yarn is 3 or less. The preferred range of the number of slipped filaments is 2 or less, more preferably 1 or less, and even more preferably 0.
[0117] The above "180m" can be any of the following lengths:
[0118] 1) The length of the glass yarn starting from the end (one end or the other end) in the longitudinal direction;
[0119] 2) The length of any part except the ends.
[0120] Specific examples of the above 2) include:
[0121] 2-1) The length is set with a location 2 to 6 m (eg, 5 m) away from the end in the longitudinal direction as the starting point.
[0122] According to 2-1), the number of slipped filaments can be accurately measured in accordance with the gist of the present invention without being affected by the "looseness" that is easily generated at the end of the glass yarn.
[0123] In the case where the glass yarn is wound onto a bobbin, "180 m" may be any of the following lengths:
[0124] 3) The length including at least a portion of the outermost or innermost circumference of the bobbin;
[0125] 4) The length of any part other than the outermost and innermost parts.
[0126] As specific examples of the above 4), from the viewpoint of ease of observation, the following can be cited:
[0127] 4-1) The length is set with the beginning of the second circle as the starting point when the outermost circumference is the first circle;
[0128] 4-2) The length is set with the start point being the beginning of the second circle when the innermost circle is the first circle.
[0129] Among them, it can be:
[0130] 4-3) The length set at any location other than the above starting point.
[0131] Taking a glass yarn having a length of more than 10,000 m as the object, when a measurement range of 180 m in the length direction is selected at 5 different locations, the number of slipped filaments in the measurement range of the 5 locations is preferably 3 or less, more preferably 2 or less, further preferably 1 or less, and most preferably 0.
[0132] In addition, taking a glass yarn having a length of more than 50,000 m as the object, when a measurement range of 180 m in the length direction is selected at 7 different locations, the number of slipped filaments in the measurement range of the 7 locations is preferably 3 or less, more preferably 2 or less, further preferably 1 or less, and most preferably 0.
[0133] In addition, taking a glass yarn having a length of more than 100,000 m as the object, when a measurement range of 180 m in the length direction is selected at 10 different locations, the number of slipped filaments in the measurement range of the 10 locations is preferably 3 or less, more preferably 2 or less, further preferably 1 or less, and most preferably 0.
[0134] When measuring the number of slipped filaments, the conveying speed of the glass yarn can be increased. In order to keep the same as the weft yarn ejection in the weaving process, the glass yarn can be pulled out from the bobbin by air and measured while being conveyed (in this case, a yarn guide is appropriately provided to prevent the ejected glass yarn from getting out of control).
[0135] The number of slipped filaments was measured according to the method described in the Examples.
[0136] By making the number of slipped filaments below the above range and the breaking strength within the above range, it is less likely that the filaments will fall off more rapidly, the filaments will break, or the coarse fluff caused by the entanglement of the broken filaments will occur during the transportation process from pulling the glass yarn from the bobbin to ejecting it. As a result, high-quality glass cloth with fewer fuzz-dense areas can be stably obtained. It is speculated that this is because: since the degree and frequency of filament slippage are small within a certain range, the degree of interference between the slippage area and the weaving components such as the ring guide or the resistance caused by the interference becomes small, so the damage caused by the interference with the weaving components can be suppressed to a small extent.
[0137] In particular, as described above, the weft yarn is easily broken, and the broken filament pieces are easily entangled due to the movement of the balloon. On the other hand, it can be inferred that by adjusting the number of falling filaments to the above range, the breakage of the filaments or the entanglement of the broken filaments can be suppressed. In addition, it can be inferred that this is because the degree and frequency of filament slippage are small within a certain range, so the degree of interference with the conveying components of the glass cloth in the fiber opening process or the resistance caused by the interference becomes small, thereby being able to suppress the damage caused by the interference with the conveying components.
[0138] The number of slipped filaments can be adjusted by the following methods alone or in combination:
[0139] In a spinning process for producing glass yarn, when filaments ejected from a plurality of bushing nozzles are gathered into a yarn bundle, a method for designing the arrangement of the bushing nozzles so that the distances from the plurality of bushing nozzles to the gathering point are equal;
[0140] A method of adjusting the nozzle shape of the sleeve nozzle according to the difference in distance from the sleeve nozzle to the focusing point;
[0141] A method of adjusting the temperature of the sleeve nozzle according to the difference in distance from the sleeve nozzle to the focusing point;
[0142] A method for adjusting the cooling temperature in the spinning process of manufacturing glass yarn;
[0143] How to adjust the tension of the cake winding;
[0144] Methods for adjusting the winding speed of the silk cake;
[0145] How to adjust the traverse when winding the yarn cake;
[0146] In the aging process of the glass yarn cake for manufacturing the glass yarn, a method for adjusting the cake winding method and aging conditions so that the moisture content and the amount of sizing agent attached to the glass yarn become more uniform over the entire length of the glass yarn;
[0147] In the twisting process of manufacturing glass yarn, the shape and weight of the wire ring are adjusted so that the load when the glass yarn is bent becomes smaller;
[0148] A method for adjusting the variation range of the number of twists per unit length to a specific range;
[0149] A method of adjusting the tension so that the change in tension is reduced during the period when the glass yarn is pulled out from the bobbin and wound onto the bobbin;
[0150] ·Methods for adjusting the balloon when twisting the yarn; and
[0151] ·Method for adjusting the winding angle of glass yarn on the bobbin.
[0152] (Glass yarn density)
[0153] The density of the glass yarn is preferably 2.2 g / cm 3 Above and less than 2.5g / cm 3 , more preferably 2.2 g / cm 3 Above and less than 2.45g / cm 3 , more preferably 2.2 g / cm 3 Above and 2.40g / cm 3 Below, more preferably 2.25g / cm3 Above and 2.4g / cm 3 the following.
[0154] If the density of glass yarn is less than 2.5g / cm 3 , in the conveying process from pulling the glass yarn off the bobbin to ejecting it, the following tendency sometimes occurs: the deviation or balloon movement in the direction perpendicular to the conveying direction tends to become large, and fuzz defects are easily generated due to interference with the loom components. However, by adjusting the number of slipped filaments to the specific range described in this embodiment, the generation of fuzz caused by interference with the loom components is suppressed, thereby stably obtaining high-quality glass cloth.
[0155] In addition, if the density of glass yarn is less than 2.5g / cm 3 , when subjected to physical loads such as high-pressure water spray pressure in the fiber opening process, the following tendency sometimes occurs: the glass cloth becomes looser, the glass cloth is prone to interfere with the conveying member, and fluff defects are easily generated due to the interference with the conveying member. However, by adjusting the number of slipped filaments to a specific range in this embodiment, the generation of fluff caused by interference with the conveying member is suppressed, thereby stably obtaining high-quality glass cloth.
[0156] On the other hand, by making the density of the glass yarn 2.2 g / cm 3 In addition, by making the density of the glass yarn 2.2g / cm 3 The density of the glass yarn can be 1cm 3 It can be calculated in the form of the density of bulk glass.
[0157] (filament length and diameter)
[0158] Glass yarn is obtained by bundling a plurality of filaments and twisting them as needed. In this case, the glass yarn is classified as glass multifilament, and the filaments (glass filaments) included in the glass yarn are classified as glass monofilaments.
[0159] Here, "slippage" of the filaments refers to not only slippage of one glass filament or slippage of several glass filaments, but also includes the case where the filaments are broken. The number of slippage filaments can be measured by the method described in the Examples.
[0160] The glass yarn is preferably a glass yarn obtained by bundling 40 to 240 glass filaments having an average diameter of 3.5 to 5.5 μm, or a glass yarn having 30 to 120 glass filaments. By using a glass yarn having an average diameter and a filament number in the above range, it is easy to manufacture a glass cloth having a thickness equivalent to 1000, 1017, 1015, 1012, 1027, 1024, 1020, 1030, 1037, 1035, 106, 1067, 1078 of a conventional E glass cloth (IPC standard (IPC-4412B): Style 1000, 1017, 1015, 1012, 1027, 1024, 1020, 1030, 1037, 1035, 106, 1067, 1078).
[0161] (Elastic coefficient of glass yarn)
[0162] The elastic coefficient of the glass yarn is preferably 50 to 70 GPa, more preferably 50 to 63 GPa, and further preferably 53 to 63 GPa. By setting the elastic coefficient to be 50 GPa or more, the rigidity of the glass yarn is improved, and fuzz is not easily generated during the manufacturing process. In addition, by setting the elastic coefficient to be 70 GPa or less, the brittleness resistance of the glass yarn is improved, and fuzz is not easily generated during the manufacturing process. Furthermore, by setting the elastic coefficient to be within the above range, there is a tendency that the glass yarn has moderate softness, and when a mechanical load is applied, the filaments are not easily broken, and fuzz and weaving defects are not easily generated.
[0163] (Composition of glass yarn components)
[0164] Constituent elements of glass yarn include silicon (Si), boron (B), aluminum (Al), calcium (Ca), magnesium (Mg), phosphorus (P), sodium (Na), potassium (K), titanium (Ti), zinc (Zn), iron (Fe) and fluorine (F).
[0165] The Si content of glass yarn is calculated according to SiO 2 In terms of conversion, it is preferably 40 to 60 mass %, more preferably 45 to 55 mass %, further preferably 47 to 53 mass %, and further preferably 48 to 52 mass %.
[0166] Si is a component forming the skeleton structure of glass yarn. By making Si content more than 40% by mass, the strength of glass yarn is more easily improved. Thus, in the subsequent processes such as the manufacturing process of glass cloth and the prepreg manufacturing using glass cloth, there is a tendency to further suppress the fracture of glass cloth. In addition, by making Si content more than 40% by mass, there is a tendency that the dielectric constant of glass cloth is further reduced. On the other hand, by making Si content less than 60% by mass, the viscosity during melting is further reduced in the manufacturing process of filaments, thus, there is a tendency to obtain glass fibers with more uniform glass composition. Therefore, the obtained filaments are not easy to produce local parts that are easy to devitrify or local parts that are difficult to remove bubbles. Therefore, the filaments are not easy to produce local parts with low strength. As a result, the glass cloth composed of the glass yarn obtained using it is not easy to break. Si content can be adjusted according to the amount of raw materials used to make the filaments.
[0167] The B content of glass yarn is based on B 2 O 3 In terms of conversion, it is preferably 15 to 40 mass %, more preferably 17 to 30 mass % or 20 to 40 mass %, further preferably 18 to 28 mass %, further preferably 19 to 26 mass %, further preferably 20 to 25 mass %, and most preferably 20.5 to 24 mass %.
[0168] By making the B content more than 15% by mass, there is a tendency for the dielectric constant to be further reduced. In addition, by making the B content more than 15% by mass, the brittleness resistance of the glass cloth is improved, and appropriate softness and ductility are imparted, so that it is not easy to produce fluff when the glass yarn contacts the yarn guide, reed and other weaving machine components. On the other hand, in order to maintain the strength of the glass yarn, the B content is preferably less than 40% by mass. In addition, by making the B content less than 40% by mass, the moisture absorption resistance is improved. The B content can be adjusted according to the amount of raw materials used to make the filaments. It should be noted that in the production of the filaments, when the conditions, amount or content may change, they can be estimated in advance and the amount of raw materials added can be adjusted.
[0169] The Al content of glass yarn is determined by the ratio of alumina (Al 2 O 3 ) conversion, preferably 11 to 18 mass %, more preferably 11 to 16 mass %, and further preferably 12 to 16 mass %. By making the Al content within the above range, there is a tendency to further improve electrical properties and strength. The Al content can be adjusted according to the amount of raw materials used to make the filaments.
[0170] The Ca content of the glass yarn is preferably 5 to 10% by mass, preferably 5 to 9% by mass, and more preferably 5 to 8.5% by mass, calculated as calcium oxide (CaO). By making the Ca content 5% or more by mass, there is a tendency that the viscosity during melting is further reduced and a glass fiber with a more uniform glass composition is obtained during the manufacturing process of the filament. In addition, by making the Ca content 10% or less by mass, there is a tendency that the dielectric constant is further improved. The Ca content can be adjusted according to the amount of raw materials used to make the filament.
[0171] The glass yarn may have excellent various properties by containing predetermined amounts of Mg, P, Na, K, Ti, Zn, Fe, and F. These contents can be adjusted according to the amounts of raw materials used to produce the filaments.
[0172] The above-mentioned contents can be measured by ICP emission spectrometry. Specifically, the Si content and the B content can be obtained by dissolving the weighed glass cloth sample with sodium carbonate, dissolving it with dilute nitric acid and fixing the volume, and measuring the obtained sample by ICP emission spectrometry. In addition, the Fe content can be obtained by dissolving the weighed glass cloth sample with an alkali dissolution method and fixing the volume, and measuring the obtained sample by ICP emission spectrometry. Furthermore, the Al content, the Ca content and the Mg content can be obtained by heating and decomposing the weighed glass cloth sample with sulfuric acid, nitric acid and hydrogen fluoride, dissolving it with dilute nitric acid and fixing the volume, and measuring the obtained sample by ICP emission spectrometry. It should be noted that as an ICP emission spectrometry device, a PS3520VDD II manufactured by Hitachi High-Technologies Corporation can be used.
[0173] (Dielectric constant of glass yarn)
[0174] The dielectric constant of the glass yarn is preferably 5.0 or less, more preferably 4.9 or less, further preferably 4.8 or less, and particularly preferably 4.6 or less at a frequency of 10 GHz. The dielectric constant of the glass yarn can be measured, for example, by a cavity resonance method. In this specification, the dielectric constant of the glass yarn refers to the dielectric constant at a frequency of 10 GHz unless otherwise specified.
[0175] (Twist interval length and twist interval length difference index of glass yarn)
[0176] The twist interval length of the glass yarn is preferably 1.8 to 10.0 cm, more preferably 1.9 to 9.9 cm, further preferably 1.95 to 4.0 cm, and most preferably 2.0 to 3.5 cm. The minimum twist interval length is preferably 1.8 cm, more preferably 1.9 cm, further preferably 1.95 cm, and most preferably 2.0 cm. The maximum twist interval length is preferably 10.0 cm, more preferably 9.9 cm, further preferably 4.0 cm, and most preferably 3.5 cm.
[0177] In addition, the value obtained by dividing the difference between the maximum value of the twist interval length of the glass yarn and the minimum value of the twist interval length by the average value of the twist interval length (twist interval length difference index) is preferably less than 0.7, more preferably less than 0.6, further preferably less than 0.5, most preferably less than 0.4, and may exceed 0. If the twist interval length and / or the twist interval length difference index of the glass yarn is within the above-mentioned numerical range, there is a tendency that when the glass yarn is wound onto a bobbin, the number of slipped filaments evaluated on the outer layer of the bobbin tends to be less than 3, and / or the number of slipped filaments over the entire length of the bobbin decreases. Although it is not intended to be bound by theory as a reason for the decrease in the number of slipped filaments, the following three reasons can be considered:
[0178] (i) If the twist interval length is greater than the lower limit, the torsional shear stress is suppressed to a small value, so that the filament is less likely to slip off;
[0179] (ii) if the twist interval length is less than the upper limit, the binding force between the filaments constituting the glass yarn is increased, so that the filaments are less likely to slip off;
[0180] (iii) When the twist interval length difference index is less than the upper limit value, the variation of the twist angle in the longitudinal direction of the glass yarn is suppressed to be small, and therefore, the filaments are less likely to slip off.
[0181] In addition, the standard deviation of the twist number of the glass yarn is preferably 0.05 to 0.20, more preferably 0.09 to 0.18.
[0182] [Method for manufacturing glass cloth]
[0183] A third embodiment of the present invention is a method for producing a glass cloth.
[0184] The present embodiment is a method for producing a glass cloth, including a step of weaving glass yarns including a plurality of filaments as warps and wefts.
[0185] The glass yarn used is as described above.
[0186] (i) TEX is 1 to 13;
[0187] (ii) a breaking strength of 0.50 to 0.80 N / tex; and
[0188] (iii) The number of filaments that slipped (the number of filaments that slipped to twice or more of the average yarn width when measuring 180 m was 3 or less.
[0189] Specifically, the manufacturing method includes the following steps: a glass yarn adjustment step of adjusting the glass yarn so that the number of slipped filaments is less than a specific number; a weaving step of weaving the adjusted glass yarn to obtain a glass cloth; and a fiber opening step of opening the glass yarn of the glass cloth. In the manufacturing method of the glass cloth, a degumming step of removing the sizing agent attached to the glass yarn of the glass cloth and a surface treatment step using a silane coupling agent may be included as needed.
[0190] Hereinafter, each step in the method for producing the glass cloth will be described in more detail.
[0191] (Glass yarn adjustment process)
[0192] The glass yarn adjustment step is a step of adjusting the glass yarn so that the number of slipped filaments is less than 3. More specifically, in the glass yarn adjustment step, if the number of slipped filaments is within the above range, the glass yarn is then used in the weaving step, and if it is outside the range, the use of the glass yarn in the glass yarn is prohibited.
[0193] Methods for measuring the number of slipped filaments include: a method of transporting glass yarn while observing the yarn width and the slipped filaments using a displacement meter using light projection such as laser or LED light; a method of transporting glass yarn and observing the yarn width and the slipped filaments while observing the shape of the glass yarn in an image, etc.
[0194] (Weaving process)
[0195] The weaving step is a step of weaving the glass yarn to obtain a glass cloth. The weaving structure of the glass cloth includes, for example, plain weave, basket weave, satin weave, twill weave and the like. Among these, the plain weave structure is more preferred.
[0196] Regarding an example of a weaving process in the manufacturing method of this embodiment, the warp yarns pulled in parallel are opened at the upper and lower parts by a jet loom, and the yarn discharged from the weft yarn storage device is sent out in the form of weft yarn by the jet flow of the nozzle and passed through the opening, thereby enabling weaving.
[0197] In the weaving process, the glass yarn to be the weft yarn is wound from the bobbin, and the glass yarn to be the weft yarn is ejected by the storage device.
[0198] The glass yarn is transported with movement in a direction different from the advancing direction accompanied by balloon movement or the like, and with interference with loom components such as yarn guides; or
[0199] Since the weft yarn is ejected and stopped repeatedly in units of the length of one weft yarn, the weft yarn is conveyed with fluctuations in tension and interference with loom components such as yarn guides.
[0200] Therefore, it is difficult to minimize the damage caused by the above-mentioned interference in the weft yarn having a large number of slipped filaments, and the obtained glass cloth may have fuzz or weaving defects.
[0201] In contrast, in the present embodiment, by using a glass yarn having a slip filament number within a specific range, the generation of fuzz or weaving defects when weaving the weft yarn can be suppressed, thereby improving the in-plane uniformity and batch-to-batch uniformity of the quality of the glass cloth. It should be noted that the weaving method is not limited to the air jet loom method, and can be a water jet loom method or a shuttle method.
[0202] The beating density of the warp and weft yarns constituting the glass cloth is preferably 30 to 120 yarns / 25 mm, more preferably 40 to 110 yarns / 25 mm, and further preferably 45 to 105 yarns / 25 mm. The beating density of the warp yarn can be controlled by adjusting the interval between the warp yarns drawn in parallel, and the beating density of the weft yarn can be controlled by the number of jets per unit time of the weft yarn from the nozzle and the flow rate of the warp yarn.
[0203] (Fiber opening process)
[0204] The fiber-opening step is a step of opening the glass yarn of the glass cloth. Examples of the fiber-opening method include a method of opening the glass yarn by spraying water (high-pressure water fiber-opening), a vibration washer, ultrasonic water, a mangle, and the like.
[0205] The thickness of the glass cloth finally obtained after the fiber opening process is preferably 5 to 60 μm, more preferably 7 to 55 μm, and further preferably 9 to 50 μm or 10 to 50 μm. By making the thickness of the glass cloth within the above range, there is a tendency to obtain a thin glass cloth with high strength. The cloth weight (weight per unit area) of the glass cloth finally obtained after the fiber opening process is preferably 5 to 55 g / m 2 , more preferably 6 to 50 g / m 2 , more preferably 7 to 48 g / m 2 .
[0206] (Degumming process)
[0207] The degumming step is a step of removing the sizing agent attached to the glass yarn of the glass cloth. As a degumming method, a method of removing the sizing agent by heating is mentioned, for example.
[0208] (Surface treatment process)
[0209] The surface treatment process is a process of surface treating the glass cloth using a silane coupling agent. In addition, as a surface treatment method, there can be listed: a method of bringing a surface treatment agent containing a silane coupling agent into contact with the glass cloth and drying it. It should be noted that the contact between the surface treatment agent and the glass cloth can be listed as: a method of impregnating the glass cloth with the surface treatment agent; a method of applying the surface treatment agent to the glass cloth using a roll coater, a die coater or a gravure coater, etc. There is no particular limitation on the drying method of the surface treatment agent, and examples thereof include hot air drying and a drying method using electromagnetic waves.
[0210] 〔Prepreg〕
[0211] The prepreg comprises the glass cloth obtained as described above and the base resin composition impregnated into the glass cloth. The prepreg comprising the glass cloth has less quality variation and a higher yield of the final product.
[0212] Prepregs can be produced by conventional methods, for example, by impregnating glass cloth with a varnish obtained by diluting a base resin such as epoxy resin with an organic solvent, volatilizing the organic solvent in a drying oven, and curing the thermosetting resin to a B-stage state (semi-cured state).
[0213] As the base resin composition, in addition to the above-mentioned epoxy resin, there can be listed thermosetting resins such as bismaleimide resin, cyanate ester resin, unsaturated polyester resin, polyimide resin, BT resin, functionalized polyphenylene ether resin, etc.; thermoplastic resins such as polyphenylene ether resin, polyetherimide resin, liquid crystal polymer (LCP) of wholly aromatic polyester, polybutadiene, fluororesin, etc.; and mixed resins thereof, etc. From the viewpoint of improving dielectric properties, heat resistance, solvent resistance and press formability, as the base resin composition, a resin obtained by modifying a thermoplastic resin with a thermosetting resin can be used.
[0214] In addition, the base resin composition may contain inorganic fillers such as silica and aluminum hydroxide; flame retardants such as bromine, phosphorus, and metal hydroxides; and silane coupling agents; heat stabilizers; antistatic agents; ultraviolet absorbers; pigments; colorants; lubricants, etc. in the resin.
[0215] 〔Printed circuit board〕
[0216] The printed circuit board preferably comprises the above-mentioned prepreg. The quality deviation of the printed circuit board comprising the above-mentioned prepreg is small, and the yield rate of the final product becomes high. In addition, the printed circuit board comprising the above-mentioned prepreg can also have the following effects: due to the excellent dielectric properties and excellent moisture absorption resistance, the influence of the use environment, especially the change of the dielectric constant in a high humidity environment, is small.
[0217] Example
[0218] Hereinafter, the present invention will be described in more detail using Examples and Comparative Examples.
[0219] 〔Physical properties of glass yarn and glass cloth〕
[0220] The physical properties of the glass yarn and glass cloth, specifically the thickness of the glass cloth, the average diameter of the filaments constituting the glass yarn, the TEX of the glass yarn, the breaking strength (tensile strength) of the glass yarn, and the beating density (weaving density) of the warp and weft yarns were measured in accordance with JIS R3420.
[0221] [Twist interval length, twist interval length difference index]
[0222] The twist number of 50 cm glass yarn was measured using a twist tester (manufactured by TEKNOS), and the length of each twist interval was calculated by dividing the measured length of 50 cm by the obtained twist number. Using this method, the twist number was repeatedly measured at 30 locations for each 50 cm, and the length of each twist interval was calculated. The length data of each twist interval at 30 locations were calculated. The length data of each twist interval at 30 locations were averaged to obtain the twist interval length.
[0223] In addition, using the average, maximum and minimum values of the twist interval length data obtained at 30 locations, the twist interval length difference index was calculated using the following formula (1) as the ratio of the difference between the maximum and minimum values of the twist interval length to the average value of the twist interval length.
[0224] Twist interval length difference index = {(maximum value of twist interval length - minimum value of twist interval length) / average value of twist interval length} × 100 (1)
[0225] 〔Standard deviation of twist number〕
[0226] The twist number of 50 cm glass yarn was measured using a twist tester (manufactured by TEKNOS) and converted into the twist number per 25 mm. The twist number per 25 mm was repeatedly measured at 30 locations using this method, and the standard deviation of the twist number data at the 30 locations was calculated.
[0227] 〔Elastic modulus〕
[0228] The elastic modulus of the glass yarn is measured by using a glass block obtained by melting and cooling the glass yarn as a test piece and by a pulse-echo-overlap method.
[0229] 〔Number of slipped filaments〕
[0230] While conveying the glass yarn at a speed of 1 m / min, a LED camera-based dimension measuring device (HIGH ACCURACY CMOS MICROMETER LS-9006MR / manufactured by Keyence Corporation) was used to observe the projection shape of the glass yarn using a monitor and continuously measure the yarn width. The yarn width of 180 m of the glass yarn was measured, and the average yarn width of the glass yarn was calculated from the obtained yarn width data. In addition, the cases where filaments slipped at more than twice the yarn width from the center of the yarn width were counted, and the total was taken as the "number of slipped filaments", that is, "the number of filaments that slipped to more than twice the average yarn width when measuring 180 m".
[0231] Here, the yarn width measurement of the size measuring device based on the LED camera method is carried out under the condition that 1934 measurement values can be obtained for every 1m. In the event of an error due to the inability to focus the LED (displaying a value of -9999), the measurement value is deleted and the average value of the yarn width and / or the number of slipped filaments are calculated.
[0232] The tension acting on the glass yarn when the glass yarn is conveyed is a value measured by a tension meter (Conrol Instruments ETPB-100-C0585 manufactured by SCHMIDT), and is 0.12 to 0.18N.
[0233] [Appearance inspection of bobbins (fluff inspection)]
[0234] The appearance of the bobbin wound with the glass yarn was visually inspected, and the number of detected fuzz (number of fuzz) was counted. This inspection was performed 50 times, and the average number of fuzz was calculated.
[0235] [Inspection of fuzz of glass yarn by applying a load to the glass yarn and evaluating it]
[0236] Using a fuzz inspection device manufactured by NIHON KAGAKU ENG, the glass yarn was fed at a speed of 1 m / min and passed through a model reed that made 450 reciprocating movements per minute and had a reed blade spacing of 0.35 mm. After the glass yarn was given hairiness, the number of fuzz produced per 180 m was counted using a sensor. In addition, the reciprocating speed of the model reed was set to 100 reciprocating movements per minute, and the number of fuzz produced per 180 m was also counted using a sensor.
[0237] [Evaluation: The quality of the fluff of glass cloth]
[0238] The effect of glass yarn quality (e.g., number of slipped filaments) on the fluff quality of glass cloth was investigated. As standard conditions for glass cloth manufacturing, the loom speed was set to 450 rpm, and the fiber opening treatment was performed using high-pressure water spray. Furthermore, the loom speed was increased (550, 600 rpm) to improve productivity, and the high-pressure water spray intensity was increased to improve properties.
[0239] The fluff quality of the glass cloth obtained in the examples, comparative examples and reference examples was evaluated by visual inspection. The fluff quality of the glass cloth was evaluated by visual inspection while the glass cloth was conveyed at a speed of 10 m / min using a cloth inspection machine for glass cloth. Here, in the previous visual inspection, the fluff and weaving defects were observed for the part where the halogen light was irradiated at right angles to the glass cloth and the light was reflected. However, in order to observe the broken filament fluff with a length of less than 1 mm with good sensitivity, white LED light was irradiated from the end side of the glass cloth in a direction parallel to the glass cloth surface and visual inspection was performed. The glass cloth on the cloth inspection board had fluff scattered all over the surface, so the state of fluff generation observed by illuminating the entire surface of the glass cloth was regarded as a whole-surface fluff defect. The fluff at the part where the fluff was generated on the entire surface was observed using an optical microscope, and a large amount of fluff caused by filament breakage of about 200 μm to 1000 μm was generated.
[0240] Taking the measurement length of 500m as the object, if there is fluff on the entire surface within 1m in the length direction of the glass cloth, the number of defects is counted as 1, and the deduction rate is calculated according to the following formula:
[0241] Deduction rate (%) = (total number of defects / 500) × 100.
[0242] [Evaluation: Evaluation of impregnation of glass cloth]
[0243] Under the environment of 23±2°C, bisphenol A epoxy resin was dissolved in benzyl alcohol to prepare a varnish for impregnation evaluation with a viscosity of 230±5mPa·s. Next, the glass cloth test piece was immersed in the varnish for impregnation evaluation, and the state of the varnish for impregnation evaluation infiltrating into the glass cloth was observed by an optical microscope while irradiating light from the lateral direction. In addition, the number of voids (parts not impregnated with the varnish for impregnation evaluation) 5 minutes after the glass cloth test piece was immersed in the varnish for impregnation evaluation was counted. At this time, the field of view of the glass cloth observed by the optical microscope was set to: about 6.5mm in the warp direction and about 9mm in the weft direction.
[0244] [Examples and Comparative Examples; Glass Yarn]
[0245] [Test Example 1]
[0246] Glass yarns A to N (low dielectric glass yarns, density 2.3 g / cm3 , elastic modulus is 61GPa), O~Q (low dielectric glass yarn, density is 2.3g / cm 3 , elastic modulus is 56GPa), R(E glass yarn, density is 2.6g / cm 3 The glass yarn of the outermost layer of the bobbin (with an elastic modulus of 74 GPa) is pulled out, and the position 5 m away from the end in the length direction is taken as the starting point T 0 , determine the number of slipped filaments.
[0247] [Test Example 2]
[0248] Next, a portion of the glass yarn of 500 m is further pulled out from the bobbin, i.e., a portion of the glass yarn which is 500 m away from the starting point T in the length direction. 0 The starting point is 500m. 500 , determine the number of slipped filaments.
[0249] [Test Example 3]
[0250] According to the above-mentioned Test Examples 1 and 2, the glass yarn is further pulled out from the bobbin,
[0251] The distance in length from the starting point T 0 The starting point is 1,000m. 1,000 ;
[0252] The distance in length from the starting point T 0 The starting point is 2,000m. 2,000 ;
[0253] The distance in length from the starting point T 0 The starting point is 5,000m. 5,000 ;
[0254] The distance in length from the starting point T 0 The starting point is 7,000m. 7,000 ;
[0255] The distance in length from the starting point T 0 The starting point is 9,000m. 9,000 ;
[0256] The distance in length from the starting point T 0 The starting point is 10,000 m. 10,000 ;
[0257] The distance in length from the starting point T 0 The starting point is 20,000m. 20,000 ;
[0258] The distance in length from the starting point T 0 The starting point is 30,000m. 30,000 ;
[0259] The distance in length from the starting point T 0 The starting point is 40,000m. 40,000 ;
[0260] The distance in length from the starting point T 0 The starting point is 50,000m. 50,000 ;
[0261] The distance in length from the starting point T 0 The starting point is 60,000m. 60,000 ;
[0262] The distance in length from the starting point T 0 The starting point is 70,000m. 70,000 ;
[0263] The distance in length from the starting point T 0 The starting point is 80,000m. 80,000 ;
[0264] The distance in length from the starting point T 0 The starting point is 100,000 m. 100,000 ;
[0265] The distance in length from the starting point T 0 The starting point is 120,000m. 120,000 ;
[0266] The number of slipped filaments was measured. The obtained results are shown in Table 1.
[0267] [Table 1-1]
[0268]
[0269] [Table 1-2]
[0270]
[0271] The glass yarns A to C, G, H, J, K, O, and P of the examples, which were twisted uniformly and gently with a small twist interval length difference index, had 3 or less slipped filaments evaluated in the outer layer portion of the bobbin.
[0272] And, at the starting point T 0 , starting point T 500 , starting point T 1,000 , starting point T2,000 , starting point T 5,000 , starting point T 7,000 , starting point T 9,000 When measuring at any starting point in the , the number of slipped filaments is always less than 3. It can be confirmed that when a glass yarn having a length of more than 10,000 m is used as the object, and a measurement range of 180 m in the length direction is selected at 5 different locations, the number of slipped filaments is 3 or less in each of the measurement ranges at the above 5 locations.
[0273] Even when a glass yarn having a length of 50,000 m or more is used as the object, when a measurement range of 180 m in the longitudinal direction is selected at 7 different locations according to the same concept as above, the number of slipped filaments in each of the 7 measurement ranges is 3 or less.
[0274] It was confirmed that even if a glass yarn having a length of more than 100,000 m was used as the object, when a measurement range of 180 m in the length direction was selected at 10 different locations according to the same purpose as above, the number of slipped filaments in the measurement range of the above 10 locations was less than 3.
[0275] On the other hand, the glass yarns D to F, I, L to N, Q, and R of the comparative examples having a large twist interval length difference index had 4 or more slipped filaments within the predetermined measurement range.
[0276] [Example 1]
[0277] The low dielectric glass yarn (TEX: 4.9, number of filaments: 100, elastic modulus: 61 GPa, glass composition: SiO 2 Converted to 51.2 mass%, Al 2 O 3 14.3 mass % in terms of CaO, 8.1 mass % in terms of MgO, 0.3 mass % in terms of B 2 O 3 Converted to 23.3 mass%, P 2 O 3 The warp and weft yarns were made of 0.1% by mass) and the weft and warp yarns were made of 65 / 25mm and 67 / 25mm respectively, respectively, under the condition that the loom speed of the air jet loom was 450 rpm (the weft yarn weaving speed was 450 yarns / minute).
[0278] In the table, for example, "at the starting point T 0 As shown in the item "Number of slipped filaments measured", in Example 1, the distance from the starting point T 0 The glass yarn has zero filament number that slips to at least twice the average yarn width during measurement of 180 m.
[0279] Next, the glass cloth was heated to remove the glue and the water pressure was adjusted to 5.0±0.1kg / cm 2 The fiber was opened by high-pressure water spray, and then the surface was treated with a silane coupling agent to produce a glass cloth with a thickness of 29 μm.
[0280] [Example 2]
[0281] The low dielectric glass yarn (TEX: 4.9, number of filaments: 100, elastic modulus: 61 GPa, glass composition: SiO 2 Converted to 51.2 mass%, Al 2 O 3 14.3 mass % in terms of CaO, 8.1 mass % in terms of MgO, 0.3 mass % in terms of B 2 O 3 Converted to 23.3 mass%, P 2 O 3 A glass cloth having a thickness of 29 μm was prepared in the same manner as in Example 1 except that the above-mentioned amount of MgO2 was 0.1% by mass.
[0282] [Example 3]
[0283] The low dielectric glass yarn (TEX: 4.9, number of filaments: 100, elastic modulus: 61 GPa, glass composition: SiO 2 Converted to 51.2 mass%, Al 2 O 3 14.3 mass % in terms of CaO, 8.1 mass % in terms of MgO, 0.3 mass % in terms of B 2 O 3 Converted to 23.3 mass%, P 2 O 3 A glass cloth having a thickness of 29 μm was prepared in the same manner as in Example 1 except that the above-mentioned amount of MgO2 was 0.1% by mass.
[0284] [Example 4]
[0285] The low dielectric glass yarn (TEX: 4.9, number of filaments: 100, elastic modulus: 61 GPa, glass composition: SiO 2 Converted to 51.2 mass%, Al 2 O 3 14.3 mass % in terms of CaO, 8.1 mass % in terms of MgO, 0.3 mass % in terms of B 2 O 3 Converted to 23.3 mass%, P 2 O 3A glass cloth having a thickness of 29 μm was prepared in the same manner as in Example 1 except that the above-mentioned amount of MgO2 was 0.1% by mass.
[0286] [Comparative Example 1]
[0287] The low dielectric glass yarn (TEX: 4.9, number of filaments: 100, elastic modulus: 61 GPa, glass composition: SiO 2 Converted to 51.2 mass%, Al 2 O 3 14.3 mass % in terms of CaO, 8.1 mass % in terms of MgO, 0.3 mass % in terms of B 2 O 3 Converted to 23.3 mass%, P 2 O 3 A glass cloth having a thickness of 29 μm was prepared in the same manner as in Example 1 except that the above-mentioned amount of MgO2 was 0.1% by mass.
[0288] [Comparative Example 2]
[0289] The low dielectric glass yarn (TEX: 4.9, number of filaments: 100, elastic modulus: 61 GPa, glass composition: SiO 2 Converted to 51.2 mass%, Al 2 O 3 14.3 mass % in terms of CaO, 8.1 mass % in terms of MgO, 0.3 mass % in terms of B 2 O 3 Converted to 23.3 mass%, P 2 O 3 A glass cloth having a thickness of 29 μm was prepared in the same manner as in Example 1 except that the above-mentioned amount of MgO2 was 0.1% by mass.
[0290] [Comparative Example 3]
[0291] The low dielectric glass yarn (TEX: 4.9, number of filaments: 100, elastic modulus: 61 GPa, glass composition: SiO 2 Converted to 51.2 mass%, Al 2 O 3 14.3 mass % in terms of CaO, 8.1 mass % in terms of MgO, 0.3 mass % in terms of B 2 O 3 Converted to 23.3 mass%, P 2 O 3 A glass cloth having a thickness of 29 μm was prepared in the same manner as in Example 1 except that the above-mentioned amount of MgO2 was 0.1% by mass.
[0292] [Example 5]
[0293] A glass cloth having a thickness of 29 μm was produced in the same manner as in Example 1 except that the loom rotation speed of the air jet loom was set to 550 rpm.
[0294] [Example 6]
[0295] A glass cloth having a thickness of 29 μm was produced in the same manner as in Example 3 except that the loom rotation speed of the air jet loom was set to 550 rpm.
[0296] [Comparative Example 4]
[0297] A glass cloth having a thickness of 29 μm was produced in the same manner as in Comparative Example 1 except that the loom rotation speed of the air jet loom was changed to 550 rpm.
[0298] [Example 7]
[0299] A glass cloth having a thickness of 29 μm was produced in the same manner as in Example 1 except that the loom rotation speed of the air jet loom was set to 600 rpm.
[0300] [Example 8]
[0301] A glass cloth having a thickness of 29 μm was produced in the same manner as in Example 3 except that the loom rotation speed of the air jet loom was set to 600 rpm.
[0302] [Comparative Example 5]
[0303] A glass cloth having a thickness of 29 μm was produced in the same manner as in Comparative Example 1 except that the loom rotation speed of the air jet loom was set to 600 rpm.
[0304] [Example 9]
[0305] By increasing the water pressure of the high-pressure water spray during the fiber opening process to 12.0±0.1kg / cm 2 A glass cloth having a thickness of 29 μm was produced in the same manner as in Example 1 except that the fiber-opening strength was increased.
[0306] [Example 10]
[0307] By increasing the water pressure of the high-pressure water spray during the fiber opening process to 12.0±0.1kg / cm 2 A glass cloth having a thickness of 29 μm was produced in the same manner as in Example 3 except that the fiber-opening strength was increased.
[0308] [Comparative Example 6]
[0309] By increasing the water pressure of the high-pressure water spray during the fiber opening process to 12.0±0.1kg / cm 2A glass cloth having a thickness of 29 μm was produced in the same manner as in Comparative Example 1 except that the fiber-opening strength was increased.
[0310] [Comparative Example 7]
[0311] By increasing the water pressure of the high-pressure water spray during the fiber opening process to 12.0±0.1kg / cm 2 A glass cloth having a thickness of 29 μm was produced in the same manner as in Comparative Example 2 except that the fiber-opening strength was increased.
[0312] [Comparative Example 8]
[0313] By increasing the water pressure of the high-pressure water spray during the fiber opening process to 12.0±0.1kg / cm 2 A glass cloth having a thickness of 29 μm was produced in the same manner as in Comparative Example 3 except that the fiber-opening strength was increased.
[0314] [Example 11]
[0315] The low dielectric glass yarn (TEX: 2.9, number of filaments: 100, elastic modulus: 61 GPa, glass composition: SiO 2 Converted to 51.2 mass%, Al 2 O 3 14.3 mass % in terms of CaO, 8.1 mass % in terms of MgO, 0.3 mass % in terms of B 2 O 3 Converted to 23.3 mass%, P 2 O 3 The warp and weft yarns were made of 0.1% by mass) and the weft and warp yarns were made of 74 / 25mm and 74 / 25mm respectively, respectively, at a loom speed of 450 rpm (weft weaving speed of 450 yarns / minute) on the air jet loom.
[0316] Next, the glass cloth was heated to remove the glue and the water pressure was adjusted to 4.0±0.1kg / cm 2 The glass cloth was opened by high-pressure water spray and then surface treated with a silane coupling agent to produce a glass cloth with a thickness of 21 μm.
[0317] [Example 12]
[0318] The low dielectric glass yarn (TEX: 2.9, number of filaments: 100, elastic modulus: 61 GPa, glass composition: SiO 2 Converted to 51.2 mass%, Al 2 O 314.3 mass % in terms of CaO, 8.1 mass % in terms of MgO, 0.3 mass % in terms of B 2 O 3 Converted to 23.3 mass%, P 2 O 3 A glass cloth having a thickness of 21 μm was prepared in the same manner as in Example 11 except that the above-mentioned amount of MgO2 was 0.1% by mass.
[0319] [Comparative Example 9]
[0320] The low dielectric glass yarn (TEX: 2.9, number of filaments: 100, elastic modulus: 61 GPa, glass composition: SiO 2 Converted to 51.2 mass%, Al 2 O 3 14.3 mass % in terms of CaO, 8.1 mass % in terms of MgO, 0.3 mass % in terms of B 2 O 3 Converted to 23.3 mass%, P 2 O 3 A glass cloth having a thickness of 21 μm was prepared in the same manner as in Example 11 except that the above-mentioned amount of MgO2 was 0.1% by mass.
[0321] [Example 13]
[0322] By increasing the water pressure of the high-pressure water spray during the fiber opening process to 10.0±0.1kg / cm 2 A glass cloth having a thickness of 21 μm was produced in the same manner as in Example 11 except that the fiber-opening strength was increased.
[0323] [Comparative Example 10]
[0324] By increasing the water pressure of the high-pressure water spray during the fiber opening process to 10.0±0.1kg / cm 2 A glass cloth having a thickness of 21 μm was produced in the same manner as in Comparative Example 9 except that the fiber-opening strength was increased.
[0325] [Example 14]
[0326] The low dielectric glass yarn (TEX: 9.8, number of filaments: 200, elastic modulus: 61 GPa, glass composition: SiO 2 Converted to 51.2 mass%, Al 2 O 3 14.3 mass % in terms of CaO, 8.1 mass % in terms of MgO, 0.3 mass % in terms of B 2 O 3 Converted to 23.3 mass%, P 2 O 3The warp and weft yarns were made of 0.1% by mass) and the weft and warp yarns were made of 52.5 / 25mm and 52.5 / 25mm respectively, respectively, at a loom speed of 450 rpm (weft weaving speed of 450 yarns / minute) on the air jet loom.
[0327] Next, the glass cloth was heated to remove the glue and the water pressure was adjusted to 6.0±0.1kg / cm 2 The fiber was opened by high-pressure water spray, and then the surface was treated with a silane coupling agent to produce a glass cloth with a thickness of 46 μm.
[0328] [Example 15]
[0329] The low dielectric glass yarn (TEX: 9.8, number of filaments: 200, elastic modulus: 61 GPa, glass composition: SiO 2 Converted to 51.2 mass%, Al 2 O 3 14.3 mass % in terms of CaO, 8.1 mass % in terms of MgO, 0.3 mass % in terms of B 2 O 3 Converted to 23.3 mass%, P 2 O 3 A glass cloth having a thickness of 46 μm was produced in the same manner as in Example 14 except that the above conditions were 0.1% by mass.
[0330] [Comparative Example 11]
[0331] The low dielectric glass yarn (TEX: 9.8, number of filaments: 200, elastic modulus: 61 GPa, glass composition: SiO 2 Converted to 51.2 mass%, Al 2 O 3 14.3 mass % in terms of CaO, 8.1 mass % in terms of MgO, 0.3 mass % in terms of B 2 O 3 Converted to 23.3 mass%, P 2 O 3 A glass cloth having a thickness of 46 μm was produced in the same manner as in Example 14 except that the above conditions were 0.1% by mass.
[0332] [Example 16]
[0333] By increasing the water pressure of the high-pressure water spray during the fiber opening process to 12.0±0.1kg / cm 2 A glass cloth having a thickness of 46 μm was produced in the same manner as in Example 14 except that the fiber-opening strength was increased.
[0334] [Comparative Example 12]
[0335] By increasing the water pressure of the high-pressure water spray during the fiber opening process to 12.0±0.1kg / cm 2 A glass cloth having a thickness of 46 μm was produced in the same manner as in Comparative Example 11 except that the fiber-opening strength was increased.
[0336] [Example 17]
[0337] The low dielectric glass yarn (TEX: 4.8, number of filaments: 100, elastic modulus: 56 GPa, glass composition: SiO 2 Converted to 49.8 mass%, Al 2 O 3 16.8 mass % in terms of CaO, 3.1 mass % in terms of MgO, 0.1 mass % in terms of B 2 O 3 Calculated as 23.9 mass%, P 2 O 3 The warp and weft yarns were made of 450 % tantalum (4.0% by mass) and 65 % tantalum (4.0% by mass) respectively. When the loom speed of the air jet loom was 450 rpm (the weft yarn weaving speed was 450 yarns / minute), a glass cloth with a warp weaving density of 65 / 25 mm and a weft weaving density of 67 yarns / 25 mm was obtained.
[0338] Next, the glass cloth was heated to remove the adhesive, and the water pressure was adjusted to 5.0 ± 0.1 kg / cm 2 The fiber was opened by high-pressure water spray, and then the surface was treated with a silane coupling agent to produce a glass cloth with a thickness of 31 μm.
[0339] [Example 18]
[0340] The low dielectric glass yarn (TEX: 4.8, number of filaments: 100, elastic modulus: 56 GPa, glass composition: SiO 2 Converted to 49.8 mass%, Al 2 O 3 16.8 mass % in terms of CaO, 3.1 mass % in terms of MgO, 0.1 mass % in terms of B 2 O 3 Calculated as 23.9 mass%, P 2 O 3 A glass cloth having a thickness of 31 μm was produced in the same manner as in Example 17 except that the above-mentioned amount of MgO2 was 0.1447 W / m (converted to 4.0 mass %).
[0341] [Comparative Example 13]
[0342] The low dielectric glass yarn (TEX: 4.8, number of filaments: 100, elastic modulus: 56 GPa, glass composition: SiO 2 Converted to 49.8 mass%, Al 2 O 3 16.8 mass % in terms of CaO, 3.1 mass % in terms of MgO, 0.1 mass % in terms of B 2 O 3 Calculated as 23.9 mass%, P 2 O 3 A glass cloth having a thickness of 31 μm was prepared in the same manner as in Example 15 except that the above conditions were 4.0% by mass.
[0343] [Example 19]
[0344] By increasing the water pressure of the high-pressure water spray during the fiber opening process to 12.0±0.1kg / cm 2 A glass cloth having a thickness of 31 μm was produced in the same manner as in Example 17 except that the fiber-opening strength was increased.
[0345] [Comparative Example 14]
[0346] By increasing the water pressure of the high-pressure water spray during the fiber opening process to 12.0±0.1kg / cm 2 A glass cloth having a thickness of 31 μm was produced in the same manner as in Comparative Example 13 except that the fiber-opening strength was increased.
[0347] [Reference Example 1a]
[0348] A low dielectric glass yarn (TEX of 14.6, 200 filaments, elastic modulus of 61 GPa, glass composition: SiO 2 Converted to 51.2 mass%, Al 2 O 3 14.3 mass % in terms of CaO, 8.1 mass % in terms of MgO, 0.3 mass % in terms of B 2 O 3 Converted to 23.3 mass%, P 2 O 3 The warp yarn and the weft yarn were used as the warp yarn and the weft yarn, and the weaving speed of the air jet loom was 450 rpm (the weft yarn weaving speed was 450 yarns / minute), so as to obtain a glass cloth with a warp weaving density of 59 yarns / 25 mm and a weft weaving density of 61 yarns / 25 mm.
[0349] Next, the glass cloth was heated to remove the glue and the water pressure was adjusted to 7.0±0.1kg / cm 2The glass cloth was opened by high-pressure water spray and then surface treated with a silane coupling agent to produce a glass cloth with a thickness of 73 μm.
[0350] 〔Reference Example 1b〕
[0351] By increasing the water pressure of the high-pressure water spray during the fiber opening process to 12.0±0.1kg / cm 2 A glass cloth having a thickness of 73 μm was produced in the same manner as in Reference Example 1a except that the fiber-opening strength was increased.
[0352] 〔Reference Example 2a〕
[0353] A low dielectric glass yarn (TEX of 19.4, 200 filaments, elastic modulus of 61 GPa, glass composition: SiO 2 Converted to 51.2 mass%, Al 2 O 3 14.3 mass % in terms of CaO, 8.1 mass % in terms of MgO, 0.3 mass % in terms of B 2 O 3 Converted to 23.3 mass%, P 2 O 3 The warp and weft yarns were made of 0.1% by mass) and the weft and warp yarns were made of 60 / 25mm and 57 / 25mm respectively, respectively, under the condition that the loom speed of the air jet loom was 450 rpm (the weft yarn weaving speed was 450 yarns / minute).
[0354] Next, the glass cloth was heated to remove the glue and the water pressure was adjusted to 7.0±0.1kg / cm 2 The glass cloth was opened by high-pressure water spray and then surface treated with a silane coupling agent to produce a glass cloth with a thickness of 89 μm.
[0355] 〔Reference Example 2b〕
[0356] By increasing the water pressure of the high-pressure water spray during the fiber opening process to 12.0±0.1kg / cm 2 A glass cloth having a thickness of 89 μm was produced in the same manner as in Reference Example 2a except that the fiber-opening strength was increased.
[0357] 〔Reference Example 3a〕
[0358] E glass yarn (TEX 5.5, 100 filaments, elastic modulus 74 GPa, glass composition: SiO 2 Converted to 53.1 mass%, Al 2 O 315.3 mass % in terms of CaO, 21.0 mass % in terms of MgO, 1.9 mass % in terms of B 2 O 3 Converted to 8.0 mass%, P 2 O 3 The glass cloth having a warp yarn weaving density of 65 yarns / 25 mm and a weft yarn weaving density of 67 yarns / 25 mm was obtained under the condition that the loom speed of the air jet loom was 450 rpm (the weft yarn weaving speed was 450 yarns / minute).
[0359] Next, the glass cloth was heated to remove the adhesive, and the water pressure was adjusted to 5.0 ± 0.1 kg / cm 2 The glass cloth was opened by high-pressure water spray and then surface treated with a silane coupling agent to produce a glass cloth with a thickness of 29 μm.
[0360] 〔Reference Example 3b〕
[0361] By increasing the water pressure of the high-pressure water spray during the fiber opening process to 12.0±0.1kg / cm 2 A glass cloth having a thickness of 89 μm was produced in the same manner as in Reference Example 3a except that the fiber-opening strength was increased.
[0362] The evaluation results of the glass yarn and glass cloth in the above examples, comparative examples and reference examples are shown in the following table. 2 )”, “±0.1(kg / cm 2 )”.
[0363] [Table 2-1]
[0364] Table 2-1
[0365]
[0366] [Table 2-2]
[0367] Table 2-2
[0368]
[0369] [Table 2-3]
[0370] Table 2-3
[0371]
[0372] [Table 2-4]
[0373] Table 2-4
[0374]
[0375] [Table 2-5]
[0376] Table 2-5
[0377]
[0378] [Table 2-6]
[0379] Table 2-6
[0380]
[0381] [Table 2-7]
[0382] Table 2-7
[0383]
[0384] [Table 2-8]
[0385] Table 2-8
[0386]
[0387] [Table 2-9]
[0388] Table 2-9
[0389]
[0390] Examples 1 to 4, Examples 11 to 12, Examples 14 to 15, and Examples 17 to 18 can produce glass cloth with excellent nap quality. The glass yarn used in these examples has a starting point T 0 The measured number of slipped filaments was 3 or less, so it can be estimated that the number of slipped filaments of the entire glass yarn wound on the bobbin was small. It was confirmed that a glass cloth with excellent pile quality can be obtained by using such a glass yarn.
[0391] In Examples 5 to 8, even when the loom rotation speed was increased from 450 rpm to 550 rpm or 600 rpm in order to improve productivity in the weaving process, the fluff quality did not significantly deteriorate, and glass cloths with relatively good fluff quality were obtained.
[0392] In Examples 9, 10, 13, 16, and 19, the water pressure of the high-pressure water spray was increased, thereby obtaining a low-dielectric glass cloth having improved impregnation while maintaining relatively good nap quality.
[0393] On the other hand, the glass cloths obtained in Comparative Examples 1 to 3, Comparative Example 9, Comparative Example 11, and Comparative Example 13 had poor nap quality.
[0394] Furthermore, in Comparative Examples 4 to 8, 10, 12, and 14, when the loom rotation speed was increased from 450 rpm to 550 rpm or 600 rpm in the weaving step or when the water pressure of the high-pressure water spray was increased in the fiber opening step, glass cloths with significantly deteriorated nap quality were obtained.
[0395] In Reference Example 1 (a, b) and Reference Example 2 (a, b), the thicknesses were 73 μm and 89 μm, respectively, which were not as thin as the glass cloths of Examples 1 to 16.
[0396] In reference example 3 (a, b) using E glass yarn, glass cloth with relatively good fluff quality can be obtained. In low dielectric glass yarns with equal TEX, if the number of slipped filaments is large, there is a tendency that the fluff quality deteriorates due to the increase in the spray pressure of high-pressure water spray (comparative examples 1 to 3, 6 to 8). In contrast, if the results of reference example 3 are seen, such a tendency is not confirmed in E glass yarn.
[0397] In Examples 1 to 4 and Comparative Examples 1 to 3, the following results were obtained: the "number of slipped filaments" better reflects the fuzz quality of the glass cloth than the "spool appearance inspection" and the "number of fuzz generated by applying a load to the glass yarn".
Claims
1. A glass cloth obtained by weaving glass yarns containing a plurality of glass filaments as warp yarns and weft yarns, The glass cloth comprises the glass yarn that meets the following conditions: (i) TEX is 1 to 13; (ii) a breaking strength of 0.50 to 0.80 N / tex; and (iii) the number of filaments slipping to more than twice the average yarn width when measuring 180 m is 3 or less, The dielectric constant of the glass yarn is less than 5.0 at a frequency of 10 GHz, Taking 500 m of the glass cloth in the longitudinal direction as the object, irradiate the white LED light along the cloth surface, observe every 1 m in the longitudinal direction, and when the number of defects is counted as 1 in the case where there is fluff on the entire surface of the cloth surface, the deduction rate expressed by the following formula is 0 to 3.5%, Deduction rate % = (total number of defects / 500) × 100%, The whole-surface fluff includes 200-1000 μm of fluff observed on the surface of the fabric using an optical microscope and caused by the breakage of the filaments.
2. The glass cloth according to claim 1, wherein The deduction rate is below 3.0%.
3. The glass cloth according to claim 1, wherein The deduction rate is below 2.9%.
4. The glass cloth according to claim 1, wherein The glass cloth has a thickness of 10 to 50 μm.
5. The glass cloth according to claim 1, comprising the glass yarn satisfying the following conditions: (i) TEX is 1.5 to 12; (ii) a breaking strength of 0.53 to 0.79 N / tex; and (iii) The number of filaments which slipped to twice or more of the average yarn width when measuring 180 m is 2 or less.
6. The glass cloth according to claim 1, comprising the glass yarn satisfying the following conditions: (i) TEX is 2.0 to 11; (ii) a breaking strength of 0.57 to 0.78 N / tex; and (iii) The number of filaments which slipped to twice or more of the average yarn width when measuring 180 m was 1 or less.
7. The glass cloth according to claim 1, comprising the glass yarn satisfying the following conditions: (i) TEX is 1 to 7; (ii) a breaking strength of 0.60 to 0.77 N / tex; and (iii) The number of filaments which slipped to twice or more of the average yarn width when measuring 180 m was 0. 8 . The glass cloth according to claim 1 , comprising the glass yarn having a twist interval length of 1.8 to 10.0 cm.
9. The glass cloth according to claim 1, comprising the glass yarn having a twist interval length difference index of 0.7 or less, wherein the twist interval length difference index is a value obtained by dividing the difference between the maximum twist interval length and the minimum twist interval length of the glass yarn by the average twist interval length.
10. The glass cloth according to claim 9, wherein The twist interval length difference index is 0.6 or less.
11. The glass cloth according to claim 9, wherein: The twist interval length difference index is 0.5 or less.
12. The glass cloth according to claim 9, wherein: The twist interval length difference index is 0.4 or less.
13. The glass cloth according to any one of claims 1 to 12, wherein Taking the glass yarn having a length of 10,000 m or more as an object, When a measurement range of 180 m in the longitudinal direction is selected at five different locations, the number of filaments that slipped to twice or more of the average yarn width is 3 or less in each of the five measurement ranges.
14. The glass cloth according to any one of claims 1 to 12, wherein Taking the glass yarn having a length of 50,000 m or more as an object, When a measurement range of 180 m in the longitudinal direction is selected at seven different locations, the number of filaments that slipped to twice or more of the average yarn width is three or less in each of the seven measurement ranges.
15. The glass cloth according to any one of claims 1 to 12, wherein Taking the glass yarn having a length of 100,000 m or more as an object, When a measurement range of 180 m in the longitudinal direction is selected at 10 different locations, the number of filaments that slipped to more than twice the average yarn width is 3 or less in each of the 10 measurement ranges.
16. A method for producing glass cloth, comprising the steps of using glass yarns containing a plurality of glass filaments as warp yarns and weft yarns and weaving them, (i) the TEX of the glass yarn is 1 to 13; (ii) the breaking strength of the glass yarn is 0.50 to 0.80 N / tex; and (iii) the number of filaments slipping to more than twice the average yarn width when measuring 180 m is 3 or less, The dielectric constant of the glass yarn is less than 5.0 at a frequency of 10 GHz, The twist interval length of the glass yarn is 1.8 to 10.0 cm, and The glass yarn has a twist interval length difference index of 0.7 or less, wherein the twist interval length difference index is a value obtained by dividing the difference between the maximum twist interval length and the minimum twist interval length by the average twist interval length.
17. The method for producing glass cloth according to claim 16, wherein: The glass cloth comprises the glass yarn that meets the following conditions: (i) TEX is 1.5 to 12; (ii) a breaking strength of 0.53 to 0.79 N / tex; and (iii) The number of filaments which slipped to twice or more of the average yarn width when measuring 180 m is 2 or less.
18. The method for producing glass cloth according to claim 16, wherein: The glass cloth comprises the glass yarn that meets the following conditions: (i) TEX is 2.0 to 11; (ii) a breaking strength of 0.57 to 0.78 N / tex; and (iii) The number of filaments which slipped to twice or more of the average yarn width when measuring 180 m was 1 or less.
19. The method for producing glass cloth according to claim 16, wherein: The glass cloth comprises the glass yarn that meets the following conditions: (i) TEX is 1 to 7; (ii) a breaking strength of 0.60 to 0.77 N / tex; and (iii) The number of filaments which slipped to twice or more of the average yarn width when measuring 180 m was 0.
20. The method for producing a glass cloth according to any one of claims 16 to 19, wherein: The TEX of the glass yarn is 1-7.
21. The method for producing a glass cloth according to any one of claims 16 to 19, wherein: The number of glass monofilaments constituting the glass yarn is 30 to 120.
22. The method for producing glass cloth according to claim 16, wherein: The twist interval length difference index is 0.6 or less.
23. The method for producing glass cloth according to claim 16, wherein: The twist interval length difference index is 0.5 or less.
24. The method for producing glass cloth according to claim 16, wherein: The twist interval length difference index is 0.4 or less.
25. The method for producing a glass cloth according to any one of claims 16 to 19, wherein: The density of the glass yarn is 2.2 g / cm 3 Above and less than 2.5g / cm 3 .
26. The method for producing glass cloth according to claim 25, wherein: The density of the glass yarn is 2.25 g / cm 3 Above and 2.4g / cm 3 the following.
27. The method for producing a glass cloth according to any one of claims 16 to 19, wherein: The elastic coefficient of the glass yarn is 50-70 GPa.
28. The method for producing a glass cloth according to any one of claims 16 to 19, wherein: The elastic coefficient of the glass yarn is 50-63 GPa.
29. The method for producing a glass cloth according to any one of claims 16 to 19, wherein: Taking the glass yarn having a length of 10,000 m or more as an object, When a measurement range of 180 m in the longitudinal direction is selected at five different locations, the number of filaments that slipped to twice or more of the average yarn width is 3 or less in each of the five measurement ranges.
30. The method for producing a glass cloth according to any one of claims 16 to 19, wherein: Taking the glass yarn having a length of 50,000 m or more as an object, When a measurement range of 180 m in the longitudinal direction is selected at seven different locations, the number of filaments that slipped to twice or more of the average yarn width is three or less in each of the seven measurement ranges.
31. The method for producing a glass cloth according to any one of claims 16 to 19, wherein: Taking the glass yarn having a length of 100,000 m or more as an object, When a measurement range of 180 m in the longitudinal direction is selected at 10 different locations, the number of filaments that slipped to more than twice the average yarn width is 3 or less in each of the 10 measurement ranges.
32. A glass yarn, wherein: (i) TEX is 1 to 13; (ii) a breaking strength of 0.50 to 0.80 N / tex; and (iii) the number of filaments slipping to more than twice the average yarn width when measuring 180 m is 3 or less, The dielectric constant of the glass yarn is less than 5.0 at a frequency of 10 GHz, The twist interval length of the glass yarn is 1.8 to 10.0 cm, and The glass yarn has a twist interval length difference index of 0.7 or less, wherein the twist interval length difference index is a value obtained by dividing the difference between the maximum twist interval length and the minimum twist interval length by the average twist interval length.
33. The glass yarn according to claim 32, wherein (i) TEX is 1.5 to 12; (ii) a breaking strength of 0.53 to 0.79 N / tex; and (iii) The number of filaments which slipped to twice or more of the average yarn width when measuring 180 m is 2 or less.
34. The glass yarn according to claim 32, wherein (i) TEX is 2.0 to 11; (ii) a breaking strength of 0.57 to 0.78 N / tex; and (iii) The number of filaments which slipped to twice or more of the average yarn width when measuring 180 m was 1 or less.
35. The glass yarn according to claim 32, wherein (i) TEX is 1 to 7; (ii) a breaking strength of 0.60 to 0.77 N / tex; and (iii) The number of filaments which slipped to twice or more of the average yarn width when measuring 180 m was 0.
36. The glass yarn according to any one of claims 32 to 35, wherein The TEX is 1-7.
37. The glass yarn according to any one of claims 32 to 35, wherein The number of glass monofilaments constituting the glass yarn is 30 to 120.
38. The glass yarn according to claim 32, wherein The twist interval length difference index is 0.6 or less.
39. The glass yarn according to claim 32, wherein The twist interval length difference index is 0.5 or less.
40. The glass yarn according to claim 32, wherein The twist interval length difference index is 0.4 or less.
41. The glass yarn according to any one of claims 32 to 35, having a density of 2.2 g / cm 3 Above and less than 2.5g / cm 3 .
42. The glass yarn according to any one of claims 32 to 35, which has an elastic modulus of 50 to 70 GPa.
43. The glass yarn according to any one of claims 32 to 35, which has an elastic modulus of 50 to 63 GPa.
44. The glass yarn according to any one of claims 32 to 35, wherein Taking the glass yarn having a length of 10,000 m or more as an object, When a measurement range of 180 m in the longitudinal direction is selected at five different locations, the number of filaments that slipped to twice or more of the average yarn width is 3 or less in each of the five measurement ranges.
45. The glass yarn according to any one of claims 32 to 35, wherein Taking the glass yarn having a length of 50,000 m or more as an object, When a measurement range of 180 m in the longitudinal direction is selected at seven different locations, the number of filaments that slipped to twice or more of the average yarn width is three or less in each of the seven measurement ranges.
46. The glass yarn according to any one of claims 32 to 35, wherein Taking the glass yarn having a length of 100,000 m or more as an object, When a measurement range of 180 m in the longitudinal direction is selected at 10 different locations, the number of filaments that slipped to more than twice the average yarn width is 3 or less in each of the 10 measurement ranges.
Citation Information
Patent Citations
Low dielectric constant glass fiber
JP1999292567A
Glass fiber yarn
JP2004115351A
Apparatus and method for producing glass yarn
JP2011140721A
Sizing agent for glass fiber and glass fiber fabric using the same
JP2013112917A
Glass composition, glass fiber, glass cloth, and method for manufacturing glass fiber
WO2018216637A1